America from the air - Moore, Robert John (Barnes & Noble, 2003)
This book introductions America from space, urban bustle and rural retreats: the northeast cradle of libbertry: the mid-atlantic states land of old, land of new: the sunbelt big skies and endless horizons: the midwest continental divide: the rocky mountain region sun, wind and earth: the desert southwest...